Workplace factors can predict the stress levels of healthcare workers during the COVID-19 pandemic: First interim results of a multicenter follow-up study - Xiong, Na-na; Fan, Teng-teng; Leonhart, Rainer; Fritzsche, Kurt; Liu, Qi; Luo, Lei; Stein, Barbara; Waller, Christiane; Huang, Mingjin; Müller, Markus M.; , The Cope-Corona Working Group (Frontiers in Public Health, 2022)
Background Research is lacking on the long-term influence of workplace factors on the mental health of health care workers during the COVID-19 pandemic. Methods We distributed two online surveys to health care workers between May and October 2020 (T1) and between February and April 2021 (T2). Perceived stress, coronavirus-related risks, and workplace factors were measured via self-report questionnaires at both time points. We conducted hierarchical linear regression to investigate the predictive factors for high stress. Results A total of 2,110 participants from seven countries and 4,240 participants from nine countries were enrolled at T1 and T2, respectively. Among them, 612 participated in both surveys. We called this cohort T1 + T2. High stress was reported in 53.8 and 61.6% of participants at T1 and T2, respectively. In cohort T1 + T2, compared with the baseline, the level of stress rose significantly (6.0 ± 2.9 vs. 6.4 ± 3.1), as did health/safety in the workplace (3.9 ± 0.8 vs. 4.2 ± 0.7). Unfortunately, we did not detect any significant difference concerning support in the workplace. Among all factors at baseline, being older than 35 [β (95% CI) = −0.92 (−1.45, −0.40)], support [−0.80 (−1.29, −0.32)], and health/safety in the workplace [−0.33 (−0.65, −0.01)] were independent protective factors, while a positive history of mental disorders [0.81 (0.26, 1.37)] and rejection in private life [0.86 (0.48, 1.25)] were risk factors for high stress at T2. Conclusion To relieve the high stress of health care workers, organizational-level approaches should be implemented, especially measures designed to enhance support, health/safety in the workplace, and to reduce the rejection of the public.